2020
DOI: 10.3390/su12218859
|View full text |Cite
|
Sign up to set email alerts
|

Strategizing Smart, Sustainable, and Knowledge-Based Development of Cities: Insights from Florianópolis, Brazil

Abstract: Unarguably, smart, sustainable, and knowledge-based development is critical for securing a livable future for our rapidly urbanizing world. The aim of this study is to generate insights into determining effective and efficient strategies to increase sustainability and innovation capabilities of cities to achieve long-term desired urban outcomes. This paper places the city of Florianópolis (Brazil) under the smart, sustainable, and knowledge-based urban development microscope. The methodological approach of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
8
0
1
Order By: Relevance
“…However, the study also revealed that in order to become a smart and sustainable city Florianópolis still needs to overcome some challenges in terms of environmental conservation, public security, urban mobility and urban infrastructure. Even so, the study concluded that knowledge-based activities contributed and are promising for Florianópolis' development (Sabatini-Marques, Yigitcanlar, Schreiner, Wittmann, Sotto & Inkinen, 2020).…”
Section: Kbud Studies and Initiatives In Brazilmentioning
confidence: 95%
“…However, the study also revealed that in order to become a smart and sustainable city Florianópolis still needs to overcome some challenges in terms of environmental conservation, public security, urban mobility and urban infrastructure. Even so, the study concluded that knowledge-based activities contributed and are promising for Florianópolis' development (Sabatini-Marques, Yigitcanlar, Schreiner, Wittmann, Sotto & Inkinen, 2020).…”
Section: Kbud Studies and Initiatives In Brazilmentioning
confidence: 95%
“…However, it can assist in solving complex problems, by providing greater interactivity, quality, and efficiency in urban services, reducing costs and improving connections between governments and society [31]. Therefore, smart cities are supported by a combination of technological infrastructure, human skills, knowledge man- [25]).…”
Section: Knowledge-based Urban Development and Smart Citiesmentioning
confidence: 99%
“…Eight interrelated aspects can positively influence the development of cities and make them smarter, namely, governance, people or communities, natural environment, infrastructure, economy, technology, management and politics, with emphasis on the fundamental role of technology for the success of all other aspects [20]. Considering a combination of knowledge and technology, smart cities are a space with knowledgeintensive activities and based on innovation, where there are integrated social cooperation routines that allow knowledge to be acquired and adapted, supported by an information and communication infrastructure capable of managing knowledge in public digital spaces to solve city problems [25,26].…”
Section: Knowledge-based Urban Development and Smart Citiesmentioning
confidence: 99%
“…The first concerns the "directionality" of governance in dealing with green priorities: what public actors and their policies, at different levels, including context-making regulations, subsidies, and taxes, should pursue [31]. Specifically, the main direction concerns the necessity to support the link between I4.0+ and circular economy (CE) solutions in LPSs, cities, and RISs, not only because CE gives digital-related technologies an enormous field of local applications and business opportunities [60]. Solutions that pursue Industry 4.0 solutions without CE would deliver further cycles of unsustainable economic growth, with our planet being unable to support it, thereby accelerating a process destined for catastrophic outcomes and jeopardizing human liveability.…”
Section: Gated Cities and Regions And Predatory Disposal Of Waste In ...mentioning
confidence: 99%
“…National or international (the EU level is exemplary in this respect) levels of policy makers must therefore push for a sustainable agenda that forces some fundamental and necessary changes, for example, in terms of alternative energy, electrification, or plastic bans [5]. The necessity of transition can develop a local sensitivity to priorities linked to the sustainable agenda and trigger collective actions that target desirable changes, matching the social, economic, and ecological conditions of the place [13,31,60].…”
Section: Conclusion and A Look Forwardmentioning
confidence: 99%